Evaluation of Quality and Acceptability of Snack (Kokoro) Produced From Synthetic Provitamin A Maize (Zea mays) Genotypes - Akinsola, Omololami Tolulope; Alamu, Emmanuel Oladeji; Otegbayo, Bolanle Omolara; Menkir, Abebe; Maziya-Dixon, Busie (Frontiers in Sustainable Food Systems, 2020)
Kokoro from provitamin A (PVA) maize genotypes, produced through conventional breeding, was studied to improve the indigenous white maize-based snack deficient in provitamin A carotenoid commonly consumed in South-western Nigeria. The chemical composition, carotenoid retention, and acceptability of Kokoro from three PVA maize genotypes and one landrace yellow maize variety (control) were estimated. Chemical composition showed significant differences (p < 0.05) in parameters with high crude fat content (23.21–32.11%). The sensory evaluation result revealed that Kokoro from DT STR SYN2-Y (control) was the most acceptable, while among the PVA Kokoro, PVA SYN HGBC1 was acceptable. The pre-processing for the estimated carotenoids (μg g−1); lutein, zeaxanthin, total β-carotene, and PVA in maize genotypes ranged from 10.38 to 12.87, 6.03 to 10.97, 3.83 to 6.18, and 5.96 to 8.43, while after processing to Kokoro, total β-carotene ranged from 1.47 to 3.10 μg g−1 and total PVA content 2.43–4.00 μg g−1. The carotenoid retention in Kokoro from PVA maize genotypes ranged from zeaxanthin 5.89–8.39%; lutein 2.74–4.45%; total β-carotene 38.24–66.14%, and total PVA 37.98–67.05%. Degradation of carotenoid was observed due to the unit operations in the processing method that led to the exposure of the food matrix to direct sunlight, heat, light, metals, and oxygen resulting in the formation of cis-isomers and loss of provitamin A quantity. The maize genotype PVASYNHGBC0 had the highest PVA value and carotenoid retention after processing. The study observed that PVA retention of Kokoro was genotype-dependent, and genotype PVASYNHGBC0 (Provitamin A maize HGA cycle zero) retained the highest carotenoid content. Also, PVASYNHGBC0 (for all the servings' size; 100 and 150 g) in all age groups had the highest percentage contribution of vitamin A to the recommended daily allowance. However, further improvement in the carotenoid content of maize genotypes is needed to enable the production of nutritious Kokoro with higher vitamin A percentage contribution and retinol equivalent.